Spatial Analysis of the Uses of a Religious Land in the city of Baquba - Mohammed Al- Kubeisi, Amjad Raheem (Journal of Tikrit University for Humanities, 2020)
The city of Baquba includes a variety of land uses, and it differs among their various activities and services, including the religious ones. This distribution among the different neighborhoods of the city where the shrines were distributed by (3) shrines and Husseiniyat (10) Husseiniyat and about (40) mosques in the neighborhoods of the city has been observed that this distribution was not subject to the planning criteria, but it was distributed based on the wishes of the population who built some of these religious centers and in order to achieve justice in distribution in order to suit the actual needs of the population of these services, the researcher came to apply some planning criteria in order to detect the surplus and the deficit in distribution and in the per capita share of them has been noted as a deficit in its services in many neighborhoods of the city in addition to the researcher's use of many statistical methods to determine concentration and dispersion in the distribution of these services in order to give a clear picture to the planners and responsible authorities in order to redistribute them in order to suit the actual needs of the population through the use of the researcher many tables and maps that produced using GIS technology.